Caracterização de fungos entomopatogênicos e controle da Mosca Negra dos citros (Aleurocanthus wlogumi Ashby, 1908) - Rocha, Elys Regina Carvalho (2015)
Currently, the citrus industry is being threatened by the black fly citrus, Aleurocanthus woglumi Ashby (Hemiptera: Aleyrodidae), originally from Asia, is considered of agricultural importance in several countries. The objective was to study the morphology and Aschersonia aleyrodis efficiency, Beauveria bassiana, Metarhizium anisopliae and Isaria sp. in controlling the black fly citrus evaluating the growth, sporulation and germination of fungi in various culture media and determining the concentration median lethal (LC50) and Time Average Lethal (LT50) of entomopathogenic fungi on A. woglumi. Leaves of citrus blackfly containing 30 nymphs each were pulverized with four species of fungi at concentration of 1 x 107 conídios.mL-1 and distilled water. The design was completely randomized with 5 treatments and 6 repetitions. The evaluations were performed for 10 consecutive days after application of fungi. After determining the most promising fungi to control the pest, vegetative growth, sporulation and germination of these were compared in three different types of medium (Complete synthetic PDA and PDA). To determine LC50 and LT50 six concentrations were used (5 x 105 , 1 x 106 , 5 x 106 , 1 x 107 , 5 x 107 and 1 x 108 conídios.mL-1) and distilled water. The design was completely randomized with seven treatments and five repetitions. The evaluations were performed for ten consecutive days after treatment application. A. aleyrodis was more efficient at a concentration of 1 x 107 conídios.mL-1 causing 85 % mortality. Fungi had better development when produced in complete medium having greater mycelial growth, production and spore germination. The fungus A. aleyrodis proved to be pathogenic to nymphs in all evaluated concentrations. While Isaria sp. had the highest mortality at concentrations of 5 x 107 and 1 x 108 conídios.mL-1, both resulting in 61.3 % of control. Regarding TL 50, the average survival values were not different for the fungi tested, following the same pattern and for A. aleyrodis the median time was 2 days and Isaria sp. 3 days, showing the efficiency of these fungi in the biological control of A. woglumi nymphs as a control alternative